Analisis Faktor-Faktor Yang Mempengaruhi Minat Masyarakat Terhadap Investasi Emas: Analisis Faktor-Faktor Yang Mempengaruhi Minat Masyarakat Terhadap Investasi Emas - Rahma, Aldra Puspita; Canggih, Clarashinta Clara (Jurnal Ekonomika dan Bisnis Islam, 2021)
The wrong mindset about gold investment creates the thought in society that gold investment is one of long term saving with high risk, multiple requirements and indeterminate. These aspects trigger the lack of gold investment interest in the society. This research aims to understand the partial influence of general knowledge, income perception and education to the gold investment interest in Jombang district society. This research used quantitative method with associative approach. The population used was the citizen in Jombang district. Sampling techniques was done by purposive sampling, while the determination of the number of sample was using Lameshow formula. The data used in this research was primary data which obtained from the online questionnaire distribution via google form. This research questionnaire used Guttman Scale measurement. In this research, the test used multiple linier regressions. This research shows that general knowledge and education aspects have positive and significant influence to the investment interest. While in the income perception aspect, it was known that there is no positive and significant influence to the investment interest.